P Pelatihan Pembuatan Minuman Kesehatan dari Tumbuhan Obat untuk Pemberdayaan Ibu-ibu Yasinan: Training on Making Health Drinks from Medicinal Plants for the Empowerment of Yasinan Mothers - Rezekiah, Arfa Agustina; Fithria, Abdi; Hafizianor, Hafizianor; Syam’ani, Syam’ani; Asysyifa, Asysyifa; Indrayatie, Eko Rini; Rinakanti, Rinakanti; Ruslan, Muhammad (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2025)
This training aims to increase the knowledge and skills of yasinan women in Kiram Village to make health drinks made from medicinal plants. Activities are carried out using lecture, demonstration and direct practice methods which are designed to provide interactive and applied learning so that participants can understand in depth the process of making health drinks and apply it independently. The evaluation results show an increase in understanding of knowledge and technology by 16.78%, meaning the successful transfer of knowledge and skills by the implementing team. In this training, there are three types of health drinks that are most popular, namely healthy turmeric and sour, healthy kencur rice, and healthy turmeric and sour plus ginger because they are easy to make, have a popular taste, and have high health benefits.  Apart from improving skills, this activity is also expected to open up economic opportunities for yasinan mothers through the production and sale of natural-based health drinks. This training supports the development of community-based small businesses that can increase family income by utilizing local medicinal plants. This training contributes to efforts to create independent villages in the health sector and improve the quality of life of the community as a whole. It is hoped that the continuation of this program will have a wider positive impact, both from the social, economic and health aspects of the Kiram Village community. This program can also be a model for community empowerment that can be replicated in other villages.